To the question on bactericidal of ultraviolet radiation as a component of the insolation of room (Environment & Health, 2019)
The purpose of the work is to establish effective doses of sun UV, as part of the insolation of premises, and to give them a hygienic assessment from the point of view of bactericidal effectiveness.Materials and methods. On the basis of monitoring satellite data about the intensity of UV radiation (280-315 nm), the intensities of UVR are calculated which penetrates into the model room of the dwelling through a 4-mm single-chamber silicate glass (transparency coefficient of glass 0,52) for 2 hours of insolation of the first half of the day.Research results. Based on the analysis of information, including regulatory and technical sources, the spectral composition of UV radiation is substantiated, which can penetrate the dwelling through window of silicate-glass.The effective doses of this factor are calculated for two-hour insolation intervals on March 22 for Kyiv (50° 27'). The effective levels of UV radiation, that has passed through the window glass, can form, during the two-hour insolation intervals of the first half of the daytime, on the enclosing surfaces of the room effective doses from 1,04 J/m2 (7-9 hours) to 2,81 J/m2 (11-13 hours ), and in the volume of the premises - from 1,94 J/m3 (7-9 hours) to 5,26 J/m3 (11-13 hours). Indicative values of effective surface and volumetric doses of ultraviolet radiation, respectively, are proposed: 49 J/m2 and 130 J/m3, to achieve 90% of the effectiveness of the bactericidal action (according to St.aureus) in the dwelling.Conclusions . The ultraviolet component of solar radiation passing through a double silicate glass window into a southeast-oriented room with the minimum required standard, according to SN No. 2605-82, the two-hour insolation duration on March 22, neither in spectral nor in energy characteristics throughout the light day can not provide 90% of the effectiveness of the bactericidal action (according to St.aureus) on the microflora in the air of residential premises and on its internal surfaces.
Keywords: insolation; ultraviolet radiation; bactericidal action; effective bactericidal surface and volume doses; hygienic regulations